Support Services Available for Kenyan Learners with Cerebral Palsy in Aid of the Performance of Activities of Daily Living - Odhiambo, Janet Auma (American Journal of Education and Learning, 2018)
The study explored the available support services for Kenyan children with cerebral palsy in aid of their performance in the Activities of Daily Living. The study adopted an exploratory design. Sample size of the study consisted of 69 respondents which included, 26 learners with Cerebral Palsy, 10 teachers in charge of learners with Cerebral Palsy, 30 parents of learners with Cerebral Palsy, 2 Physiotherapists, and 1 Occupational therapist. Convinience and Purposive sampling precedures were used for selection of respondents. Instruments used for data collection included observation, interviews and Focus Group Discussions. The study findings showed that, learners with Cerebral Palsy depend so much on their peers with mild disabilities for survival. There were insufficient assistive devices such as wheelchairs, crutches, walkers and prosthetic devices. There were insufficient professional medical speacialists such as Physiotherapists, Occupational therapists and Speect therapists to work with learners with Cerebral Palsy. Services provided by speech therapists was a significant deficit in the study.While the support systems in the institutions were not enough, those at home were worse. The study recommendsations include: The government, Institutional Authority and Non Governmental Organizations should provide support services and Intitutional support systems to learners with Cerebral Palsy. The parents of learners with Cerebral Palsy should be made aware of the available support services for their children and how to access them. More of Physiotherapists, Occupational therapists and Speech therapists should be trained and posted to schools for learners with physical disabilities.